Nanopore Sensors: Manipulating Electrical and Fluidic Access in Integrated Nanopore‐Microfluidic Arrays Using Microvalves (Small 10/2017). Issue 10 (8th March 2017) - Tahvildari, Radin; Beamish, Eric; Briggs, Kyle; Chagnon‐Lessard, Sophie; Sohi, Ali Najafi; Han, Shuo; Watts, Benjamin; Tabard‐Cossa, Vincent; Godin, Michel
Abstract : In article number 1602601, Michel Godin and co‐workers demonstrate that on‐chip microvalves enable the regulation of electrical and fluidic access to an array of nanopore sensors integrated within microfluidic networks. Using a single pair of electrodes, multiple independent nanopores are fabricated in situ by a controlled breakdown process and are used to interrogate biomolecular samples compartmentalized within a single device equipped with microvalves.